Vern Yip's design wise : your smart guide to a beautiful home - Yip, Vern (Running Press, 2016)
Have you ever wondered exactly how high to hang your artwork? How about the light fixture over your dining table? Do you know how to ideally size a rug for any room, or the best way to arrange your furniture? Trusted designer Vern Yip answers these questions, and more, by revealing the right formulas and measurements that can make any room feel just "right." And once you know these key design principles, you're free to confidently create a home that uniquely celebrates your needs and style. Vern shares his favorite insider tips, and opens his doors to show how he's made them work in his own beloved homes. Vern Yip's Design Wise provides both the inspiration and the clear, essential guidelines you need to create a home that perfectly reflects you.